2022
DOI: 10.3390/cancers14164051
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Management in the Primary Prevention of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most frequent primary hepatic malignancy and a leading cause of cancer-related death globally. HCC is associated with an indolent clinical presentation, resulting in frequent advanced stage diagnoses where surgical resection or transplant therapies are not an option and medical therapies are largely ineffective at improving survival. As such, there is a critical need to identify and enhance primary prevention strategies to mitigate HCC-related morbidity and mortality. Obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 178 publications
(174 reference statements)
0
13
0
Order By: Relevance
“…Despite the advances in recognition of HCC and its aetiologies, 5‐year survival rate of this cancer is only 21% 81 . Hepatitis C virus (HCV) infection, hepatitis B virus (HBV) infection, alcoholic cirrhosis, aflatoxin‐contaminated food consumption, NASH, metabolic disorders and MAFLD are among the significant risk factors of HCC 82,83 . The risk factors of HCC usually contribute to liver injury by inducing chronic liver inflammation.…”
Section: Gdf11 In Liver‐associated Diseasesmentioning
confidence: 99%
“…Despite the advances in recognition of HCC and its aetiologies, 5‐year survival rate of this cancer is only 21% 81 . Hepatitis C virus (HCV) infection, hepatitis B virus (HBV) infection, alcoholic cirrhosis, aflatoxin‐contaminated food consumption, NASH, metabolic disorders and MAFLD are among the significant risk factors of HCC 82,83 . The risk factors of HCC usually contribute to liver injury by inducing chronic liver inflammation.…”
Section: Gdf11 In Liver‐associated Diseasesmentioning
confidence: 99%
“…This dietary approach—rich in vegetables and antioxidants—has “healthy” consequences on the remodeling of the gut microbiota by promoting the growth of good bacteria that promote SCFA synthesis and degrade toxic metabolites [ 86 ]. Overall, the prevention of these diseases may be related to the prevention of MAFLD progression [ 87 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Bariatric metabolic surgery can result in sustained weight loss in obese patients, while improving insulin resistance, T2DM (92% remission rate), dyslipidaemia (76% remission rate), OSA (96% remission rate), inflammation, hypoxia, oxidative stress, non-alcoholic fatty liver disease (NAFLD) and cardiovascular risk factors (58% remission rate) [ 32 ]. Consequently, observational studies have suggested a reduction in cancer incidence following bariatric surgery for morbid obesity, particularly in future gynaecological malignancies (endometrial, ovarian and breast cancer) but also in some non-hormone-associated cancers [ 33 ].…”
Section: Introductionmentioning
confidence: 99%